1993
DOI: 10.1159/000236479
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Preparation of Antisera to Ovine IgE

Abstract: Elevated levels of ovine reaginic antibody were induced by immunization with Ascaris suum antigens. The PCA activity of this antibody persisted in the skin of sheep for 20 days and was abolished by heating to 56 °C, suggesting that it was immunoglobulin E. Attempts to isolate IgE from this hyperimmune serum by gel filtration, ion exchange and affinity chromatography resulted in the preparation of a PCA-positive fraction containing proteins with molecular weights of 70,56 and 22 kD on SDS-PAGE. This preparation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

1995
1995
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…Further evidence for the specificity of this monoclonal was provided by the demonstration of a single, but diffuse, reactive band on Western blots of serum or gastric lymph of about 80 kDa as described previously for 1E7 on lymphocyte extracts (Kooyman et al 1997). Similar broad bands on SDS-PAGE have been noted for ovine epsilon chain with MW 81-96Kd (Shaw et al 1996), although this is heavier than reported by Yilmaz et al (1993) of 70-72Kd, or by Clarke & Beh (1994) of 68Kd, but consistent with molecular weights reported for mouse (Ishizaka 1985), human myeloma (Ikeyama et al 1986 circumcincta L3, or for ten days during a secondary immune response in sheep previously repeatedly infected, treated with anthelmintic, and then given a challenge of 50 000 T. circumcincta L3. Reasons for the inability to adequately detect native ovine IgE in solution by ELISA was unclear since MoAbs recently produced by Shaw et al (1996) readily detect ovine IgE in a double-antibody capture ELISA.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Further evidence for the specificity of this monoclonal was provided by the demonstration of a single, but diffuse, reactive band on Western blots of serum or gastric lymph of about 80 kDa as described previously for 1E7 on lymphocyte extracts (Kooyman et al 1997). Similar broad bands on SDS-PAGE have been noted for ovine epsilon chain with MW 81-96Kd (Shaw et al 1996), although this is heavier than reported by Yilmaz et al (1993) of 70-72Kd, or by Clarke & Beh (1994) of 68Kd, but consistent with molecular weights reported for mouse (Ishizaka 1985), human myeloma (Ikeyama et al 1986 circumcincta L3, or for ten days during a secondary immune response in sheep previously repeatedly infected, treated with anthelmintic, and then given a challenge of 50 000 T. circumcincta L3. Reasons for the inability to adequately detect native ovine IgE in solution by ELISA was unclear since MoAbs recently produced by Shaw et al (1996) readily detect ovine IgE in a double-antibody capture ELISA.…”
Section: Discussionsupporting
confidence: 72%
“…Further evidence for the specificity of this monoclonal was provided by the demonstration of a single, but diffuse, reactive band on Western blots of serum or gastric lymph of about 80 kDa as described previously for 1E7 on lymphocyte extracts ( Kooyman et al 1997 ). Similar broad bands on SDS‐PAGE have been noted for ovine epsilon chain with MW 81–96Kd ( Shaw et al 1996 ), although this is heavier than reported by Yilmaz et al (1993 ) of 70–72Kd, or by Clarke & Beh (1994) of 68Kd, but consistent with molecular weights reported for mouse ( Ishizaka 1985), human myeloma ( Ikeyama et al 1986 ) and dog ( DeBoer et al 1993 ) epsilon chain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As listed in table 2, the molecular mass of the IgE 8 chains ranges from 69 to 73 kDa [21][22][23] in humans, 68 kDa in rats [3], and 75 kDa in mice [24], The polyclonal IgE e chains, with a similar molecular mass to those identified from monoclonal IgE antibodies, were recently purified and identified in sheep [6] and dogs [5] (table 2). Because of variations in the methods used, variations among laborato ries, and even variations among experiments, it is difficult to make comparisons between the molecular masses of the 8 chains from different studies.…”
Section: Cross-reactivity Of Ige Antibodiesmentioning
confidence: 99%
“…The extremely low serum con centrations of IgE have limited the purification of polyclo nal IgE. To date, IgE e chains have been identified only from the polyclonal antibodies of dogs [5] and sheep [6], The cross-reactivity of IgE among different species is an impor tant aspect o f studies o f comparative immunology, IgE mo lecular structure, and identification of IgE in species in which IgE has yet to be identified. Previous studies have…”
Section: Introductionmentioning
confidence: 99%